PENGENDALIAN BANJIR DI SUNGAI LUSI MENGGUNAKAN CHECK DAM KAYU DI SUNGAI ORDE 1 DAN 2 - Amanatullah Savitri; Arief Wahyu Indriawan; Sri Eko Wahyuni; Suseno Darsono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Flooding is a situation where areas not normally inundated with water such as residential, industrial areas, and other public facilities to be flooded. The situation is highly detrimental to both moral and material such as transport delays which impact on the rate of the economy of a region. Flooding problems that occurred in the Regency of Grobogan is partly due to overflowing, one of the river is the Lusi river. Lusi river have a length of about 161,13 km starting from Bulu Regency Rembang downstream to the estuary through meet Serang River at Penawangan Regency Grobogan.. Lusi river conditions experience narrowing and shallowing flow leads to reduced capacity to cross the river flood discharge flow. Lusi river can no longer accommodate the flood discharge that occured especially in the rainy season so that commemorate the area around the Lusi river. In addition, the floods also caused the creek bank that opened for the access road so the water From studies and calculations have been done using the help of HEC-HMS, AutoCAD Civil 3D and ArcGIS software to show the impact of the flood discharge and long sectional to determine whether or not cross-river improvements. Lusi River flooding problems addressed in using wooden check dam in river order 1 and 2 in Lusi watershed.